Loss to follow up of pregnant women with HIV and infant HIV outcomes in the prevention of maternal to child transmission of HIV programme in two high-burden provinces in Papua New Guinea: a retrospective clinical audit. Issue 12 (12th December 2020) - Kelly-Hanku, Angela; Nightingale, Claire Elizabeth; Pham, Minh Duc; Mek, Agnes; Homiehombo, Primrose; Bagita, Mary; Nankinga, Justine; Vallely, Andrew; Vallely, Lisa; Sethy, Ghanashyan; Kaldor, John; Luchters, Stanley
Abstract : Introduction: Despite early adoption of the WHO guidelines to deliver lifelong antiretroviral (ARV) regimen to pregnant women on HIV diagnosis, the HIV prevention of mother to child transmission programme in Papua New Guinea remains suboptimal. An unacceptable number of babies are infected with HIV and mothers not retained in treatment. This study aimed to describe the characteristics of this programme and to investigate the factors associated with programme performance outcomes. Methods: We conducted a retrospective analysis of clinical records of HIV-positive pregnant women at two hospitals providing prevention of mother to child transmission services. All women enrolled in the prevention of mother to child transmission programme during the study period (June 2012–June 2015) were eligible for inclusion. Using logistic regression, we examined the factors associated with maternal loss to follow-up (LTFU) before birth and before infant registration in a paediatric ARV programme. Results: 763 of women had records eligible for inclusion. Demographic and clinical differences existed between women at the two sites. Almost half (45.1%) of the women knew their HIV-positive status prior to the current pregnancy. Multivariate analysis showed that women more likely to be LTFU by the time of birth were younger (adjusted OR (AOR)=2.92, 95% CI 1.16 to 7.63), were newly diagnosed with HIV in the current/most recent pregnancy (AOR=3.50, 95% CI 1.62 to 7.59) and were in an HIV serodiscordant relationship (AOR=2.94, 95% CI 1.11 to 7.84). Factors associated with maternal LTFU before infant registration included being primipara at the time of enrolment (AOR=3.13, 95% CI 1.44 to 6.80) and being newly diagnosed in that current/most recent pregnancy (AOR=2.49, 95% CI 1.31 to 4.73). 6.6% (50 of 763) of exposed infants had a positive HIV DNA test. Conclusions: Our study highlighted predictors of LTFU among women. Understanding these correlates at different stages of the programme offers important insights for targets and timing of greater support for retention in care.